2013
DOI: 10.1590/s0100-29452013000400019
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do porta-enxerto e da época de poda na duração das fases fenológicas e no acúmulo de graus-dia pela videira 'Niagara Rosada'

Abstract: RESUMO-Avaliaram-se a influência dos porta-enxertos 'IAC 766', 'IAC 572', 'IAC 313', 'IAC 571-6' e 'Ripária do Traviú' e da época de poda na duração dos estádios fenológicos e no acúmulo de graus-dia pela videira 'Niagara Rosada'. O experimento foi realizado em Louveira-SP. Os tratamentos consistiram na combinação de cinco porta-enxertos e três épocas de poda, sendo utilizado o delineamento experimental em blocos inteiramente casualizados, com parcelas subdivididas e cinco repetições, sendo as parcelas represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Research has already been done on the effect of the rootstock on dates and length of the grapevine phenology stages in other conditions, such as different soils, climates, cultural practices and genetic materials (SATO et al, 2008;TECCHIO et al, 2011TECCHIO et al, , 2013LOUREIRO et al, 2016). Other aspects of phenology were also studied as well as the effect of the pruning time (MURAKAMI et al, 2002;BRIGHENTI et al, 2015), maturity and harvest of the grapes out of season (SATO et al, 2008) and at two grape harvests per year (ANZANELLO et al, 2012).…”
Section: Dates Of Phenology Stages Number Of Days Between Each Stagementioning
confidence: 99%
See 2 more Smart Citations
“…Research has already been done on the effect of the rootstock on dates and length of the grapevine phenology stages in other conditions, such as different soils, climates, cultural practices and genetic materials (SATO et al, 2008;TECCHIO et al, 2011TECCHIO et al, , 2013LOUREIRO et al, 2016). Other aspects of phenology were also studied as well as the effect of the pruning time (MURAKAMI et al, 2002;BRIGHENTI et al, 2015), maturity and harvest of the grapes out of season (SATO et al, 2008) and at two grape harvests per year (ANZANELLO et al, 2012).…”
Section: Dates Of Phenology Stages Number Of Days Between Each Stagementioning
confidence: 99%
“…Other studies on GDD were carried out in different places, grapevine varieties or cultural practices (ROBERTO et al, 2004;NEISS et al, 2010;ANZANELLO et al, 2012;TECCHIO et al, 2013;BRIGHENTI et al, 2015;NUNES et al, 2016;CARVALHO, 2016). There are differences between the results of these trials and those of the present study, which are mainly due to terroir, cultural practices and genetic material used in the experiments.…”
Section: Heat Requirement To Ripen the Grapementioning
confidence: 99%
See 1 more Smart Citation
“…Although, rootstock is known for its vigor, several studies have shown that rootstocks differ in their effect on water and nutrient absorption capacity in the grafted variety, since there is selectivity in ion movement in soil and root absorption, according to each variety (Tecchio et al, 2011). Each rootstocks may interact differently with grape vine's fruits phenology, degree-day accumulation, yield, quality (Motta et al, 2009;Rizk-Alla et al, 2011;Jogaiah et al, 2013;Tecchio et al, 2013;Tofanelli et al, 2011); plants physiology (Cookson and Ollat, 2013); soaked and saline soils tolerance (Jogaiah et al, 2014); plant resistance to drought (Serra et al, 2014); and disease resistance (Billones-Baaijen et al, 2014, Murolo andRomanazzi, 2014). Besides the combination of rootstocks and canopy conductance can affect water and nutrient uptake in grape vines (Bavaresco and Lovisolo, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Essa quantidade de energia é normalmente expressa em graus-dia (GD), que é a diferença entre a temperatura média ambiente e a temperatura-base (valor abaixo do qual não ocorre desenvolvimento) (SATO et al, 2008). O conhecimento das necessidades térmicas permite que o viticultor faça um planejamento da duração do ciclo de produção e a provável data de colheita, de acordo com os dados climáticos de cada região e a demanda térmica de cada variedade (TECCHIO et al, 2013).…”
Section: Introductionunclassified